Ferric Oxide Mediated Formation of PCDD/Fs from 2-Monochlorophenol - Nganai, Shadrack (2009)
The copper oxide, surface-mediated formation of polychlorinated dibenzop-dioxins and dibenzofurans (PCDD/F) from precursors such as chlorinated phenols is considered to be a major source of PCDD/F emissions from combustion sources. In spite of being present at 2–50x higher concentrations than copper oxide, virtually no studies of the iron oxide-mediated formation of PCDD/F have been reported in the literature. We have performed packed bed, flow reactor studies of the reaction of 50 ppm gas phase 2-monochlorophenol (2-MCP) over a surface of 5% iron oxide on silica over a temperature range of 200–500 °C. Dibenzo-p-dioxin (DD), 1-monochlorodibenzo-p-dioxin (1-MCDD), 4,6-dichlorodibenzofuran (4,6-DCDF), and dibenzofuran (DF) were formed in maximum yields of 0.1, 0.2, 0.3, and 0.4 %, respectively. The yield of PCDD/F over iron oxide peaked at temperatures 50–100 °C higher in temperature than over copper oxide. The maximum yields of DD, 1-MCDD and 4,6-DCDF were 2x and 5x higher over iron oxide, respectively, than over copper oxide, while DF was not observed at all for copper oxide. The resulting PCDD/PCDF ratio was 0.39 versus 1.2 observed for iron oxide and copper oxide, respectively, which is in agreement with PCDD to PCDF ratios in full-scale combustors that are typically ≪1. The combination of 2–50x higher concentrations of iron oxide than copper oxide in most full-scale combustors and 2.5x higher yields of PCDD/F observed in the laboratory, suggest that iron oxide may contribute as much as 5–125x more than copper oxide to the emissions of PCDD/F from full-scale combustors.